Visual search strategies in expert and novice drivers during the per-ception of driving scenes - Gómez-Valadés, Juan Miguel; Luis, Vicente; Reina, Raúl; Sabido, Rafael; Moreno, Francisco Javier (Anales de Psicología / Annals of Psychology, 2013)
The aim of this study is to analyze the visual search strategies of expert (n=5) and inexperienced drivers (n=5) during a simulated task of driving in laboratory. The ocular movements are recorded with an ASL SE5000 eye tracking system; and the number, time and location of these fixations are analyzed too. The drivers observed a sequence of specific frames of driving, and then they had to respond with a verbal respond after each trial. The results show that the expert and inexperienced group develop different visual search strategies. These differences are the higher time of fixation, independently of location fixation; and even the higher number and time of fixation on relevant stimuli during the driving (vertical signs and vehicles) in the expert group against to other group. Instead, the inexperienced group shows higher number and time on irrelevant stimuli during the driving. There are no differences between groups of drivers on the accuracy of their verbal response, and neither there is any relation between perceptual variables and the accuracy of their responses.